A Comprehensive Review of Key Cyber-Physical Systems, and Assessment of Their Education Challenges - Imre Kocsis; Boglarka Burjan-Mosoni; Istvan Balajti (IEEE Access)
The importance of cyber-physical systems (CPS) continues to grow today, with AI applications in the CPS design principles that formulate smart cyber-physical systems (S-CPS). These called Extended Cyber-Physical Systems (E-CPS) or Next Generation Cyber-Physical Systems (NG-CPS) are expanding to address more complex problems such as the impact of intellectualization on human roles and the social embedding of heterogeneous systems. The industrial metaverse for smart manufacturing and its novel characteristics require new types of advanced cyber-physical coordinated situational awareness and active defense against cyber-attacks. These new challenges raise the profile of engineering education at the university level, while the addition of new skills requires rigorous preparatory work and the development of tailored requirements for effective knowledge transfer methods that meet the educational needs of the current environment. Students need to be prepared to manage information and influence decision-makers effectively. This article presents a pedagogical approach to teaching CPS as an advanced undergraduate subject by integrating elements of competency and personal development into daily classroom activities. This reflects the circumstances and demands of everyday engineering work, focusing on soft skills such as time management, precision, accuracy, focus, communication, teamwork, and also applying the methods of continuous accountability and reward. The specific tasks and assessment techniques simulate real-life situations in the industry, and R&D activities, where the students became efficient engineers, researchers and later on could fulfil the position of reliable BOSSs. The conclusions are based on individual and group interviews conducted with students in Hungarian and international mechatronics undergraduate programs.